Student aid and the distribution of educational attainment - Maggie Jones (Queen's University, Department of Economics, 2016)
I examine the effect of student aid on the distribution of educational attainment in the context of a post-secondary funding program for Indigenous students in Canada. I show that student aid programs targeted at marginalized groups can increase average educational attainment; however, these benefits are driven by an increase in college training, not in the number of university degrees. For students living in remote communities that face above average costs to graduating high school, the elimination of post-secondary funding programs can have adverse effects on high school graduation rates, highlighting the importance of considering the effect of student aid on the entire distribution of educational attainment.
Keywords: I21; I22; I28; J15; 330; Education; post-secondary funding; student aid; education choice